(untitled) (The Journal of Plant Protection Sciences, 2021)
Trichoderma has gained maximum attention as biocontrol agent due to the fact that it is effective against a large number of soil-borne plant pathogenic fungi, suppressive effects on some root nematodes without adversely affecting beneficial microbes like Rhizobium and capable of promoting growth of certain crops. There are two major methods of inoculum production of Trichoderma spp. viz., solid state fermentation and liquid state fermentation. In solid fermentation, the fungus is grown on various cereal grains, agricultural wastes and byproducts. The solid state production is highly labour intensive and fit for cottage industry. These products are used mainly for direct soil application in nurseries/main fields to suppress the soil-borne inoculum. In liquid state fermentation, Trichoderma is grown in inexpensive media like molasses and yeast medium in deep tanks on a commercial scale. Biomass from the liquid fermentation can be made into different formulations like, dusts, granules, pellets, wettable powders. Trichoderma formulations can be applied to the seed either by dry seed treatment or by seed biopriming for control of several soil-borne diseases of some field crops. Similarly, seedlings of horticultural crops and rice are treated by dipping the roots in Trichoderma suspensions before planting. Granular or pellets preparations and Trichoderma enriched FYM have been used for soil application directly and have provided effective control of diseases both nurseries and field conditions. To ensure that the products of Trichoderma do not affect the environment, human beings and other living organisms adversely and to prevent the sale of poor quality products to the farmers, the Central Insecticide Board of Government of India has made registration of microbial pesticides mandatory before commercial production/import/sale. Guidelines and data requirements for registration of microbial pesticides have been provided in the annexure of Insecticide Act. Quality control parameters set by CIB are inadequate for knowing potentiality of a bioagent. Apart from the counts of live propagules in the formulation, bioefficacy also should be taken as a quality parameter to ensure availability of better products to farmers.